Lugdunum christianum Lyon du IVe au VIlle s. : topographie nécropoles et édifices religieux - Reynaud, Jean-François (Documents d'archéologie française, 1998)
Archaeological research carried out in Lyon since 1971 at three major sites, the cathedral complex and the churches and graveyards of Saint-Just and Saint-Laurent-de-Choulans, has changed our understanding of the topography of the town during the early Christian period. Lyon, federal capital of the Cauls and later capital of the Burgundian kings. was from the IVth to VIIIth centuries an ecclesiastical centre of prime importance. The remains oftwo churches and of a baptistery forming an épiscopal group (one of the first to be completely excavated). the basilicas built on the tombs of saints and the graveyards, are evidence of the creation of a new Christian architecture, respecting antique traditions, and of the Christianisation of funerary practices. Thorough analysis of the archaeological evidence, confronted with archivai sources and documents, confirms the vitality and prestige of Lugdunum christianum.